Impact of Web-Based Reservation Implementation on Patient No-Show Mediated by Waiting Time - Dian Andriani; Yunizar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study investigates the impact of a web-based reservation system on patient no-show rates at Cipanas Garut Clinic, where high no-show rates and long waiting times hinder service efficiency. The objectives are to assess the system’s effectiveness in reducing no-shows, shortening waiting times, and evaluating waiting time as a mediating factor. Using a quantitative approach guided by the Technology Acceptance Model and the Unified Theory of Acceptance and Use of Technology, data were collected through purposive sampling from 119 patients who used the reservation system between March and May 2025. A questionnaire measured perceptions of the reservation system, waiting time, and no-show behavior, analyzed using Structural Equation Modeling–Partial Least Squares. The findings reveal that the web-based reservation system significantly reduces no-show rates by enhancing scheduling efficiency and transparency, with waiting time partially mediating this relationship. Patients reported high satisfaction with the system’s accessibility and reduced waiting times, improving attendance. The study concludes that web-based reservation systems offer a viable solution for primary healthcare facilities to enhance operational efficiency and patient satisfaction, with implications for adopting digital tools and optimizing waiting time management in resource-constrained settings.